Mediating effects of workgroup processes on the relationship between nurse turnover and nurse outcomes in hospitals - Bae, Sung-Heui; Kim, Suin; Myung, Hwasook (Frontiers in Public Health, 2023)
Background: Nurse turnover is often considered to be an outcome, and few studies have investigated its consequences in nursing care. The underlying mechanism of the nurse turnoverandnurse outcome relationships has not been empirically investigated. Therefore, this study examines the workgroup processes and nurse outcomes as the consequences of nurse turnover and the mediating effect of the workgroup processes on the nurse turnover-andnurse outcomes relationship.Methods: A cross-sectional design was adopted to investigate the data collected from 33 nurse managers and 2264 staff nurses. Furthermore, six-month turnover rates, workgroup processes (nurse–nurse collaboration, team cohesion), and nurse outcomes (job satisfaction, intent to leave) were utilized in the multivariate regression models.Results: Overall, 536 (24.42.5%) nurses had worked in nursing units with a zero six-month turnover rate for the last six months. The average mean six-month turnover rate for the six months was 15.56%. Nurse turnover adversely affected nurses' job satisfaction and several subscales of team cohesion that includinge task cohesion and social cohesion. Team cohesion partially mediated the relationship between nurse turnover and job satisfaction.Nurse turnover decreased job satisfaction and team cohesion, and team cohesion partially mediated the nurse turnover-and nurse outcomes relationships. These findings provide evidence supporting the significant adverse effects of nurse turnover and also suggest the potential role of workgroup processes into explaining the underlying mechanism of the relationship between nurse turnover and nurse outcomes relationships.Implications for nursing and health policy: Healthcare organizations must create a positive work environment to reduce nurse turnover. Further, states and countries should try to develop and establish nursing and health policies to prevent turnover.